Fruit buds of the genus, prunus: their structure as affecting productiveness - Hall, William Logan (My University, 1898)
Introduction: Soon after the discovery of the process of fertilization among plants it was noted that certain differences in vigor and quality resulted in the offspring when a plant was fertilized by pollen from a distinct individual. The first facts pointing toward a general law were observed by investigators in the latter part of the eighteenth and the beginning of the nineteenth centuries. Andrew Knight approached the truth when he said, “Nature has something more in view than that its own males should fecundate each blossom.” Kobrenter, Sprengel, and Muller understood something of the same law and added point after point, but without explaining very definitely the relations between the facts they noted.
Citation: Hall, William Logan. Fruit buds of the genus, prunus: their structure as affecting productiveness. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Fertilization; Pollen; Nature; Blossom; Andrew Knight; Theses